Double- and Triple-Duty Caregiving Men: An Examination of Subjective Stress and Perceived Schedule Control. (April 2018) - DePasquale, Nicole; Zarit, Steven H.; Mogle, Jacqueline; Moen, Phyllis; Hammer, Leslie B.; Almeida, David M.
Based on the stress process model of family caregiving, this study examined subjective stress appraisals and perceived schedule control among men employed in the long-term care industry (workplace-only caregivers) who concurrently occupied unpaid family caregiving roles for children (double-duty child caregivers), older adults (double-duty elder caregivers), and both children and older adults (triple-duty caregivers). Survey responses from 123 men working in nursing home facilities in the United States were analyzed using multiple linear regression models. Results indicated that workplace-only and double- and triple-duty caregivers' appraised primary stress similarly. However, several differences emerged with respect to secondary role strains, specifically work–family conflict, emotional exhaustion, and turnover intentions. Schedule control also constituted a stress buffer for double- and triple-duty caregivers, particularly among double-duty elder caregivers. These findings contribute to the scarce literature on double- and triple-duty caregiving men and have practical implications for recruitment and retention strategies in the health care industry.